Identification of Dietetically Absorbed Rapeseed (Brassica campestris L.) Bee Pollen MicroRNAs in Serum of Mice. (15th August 2016) - Chen, Xuan; Dai, Guan-hai; Ren, Ze-ming; Tong, Ye-ling; Yang, Feng; Zhu, Yong-qiang
Abstract : MicroRNAs (miRNAs) are a class of small noncoding RNA that, through mediating posttranscriptional gene regulation, play a critical role in nearly all biological processes. Over the last decade it has become apparent that plant miRNAs may serve as a novel functional component of food with therapeutic effects including anti-influenza and antitumor. Rapeseed bee pollen has good properties in enhancing immune function as well as preventing and treating disease. In this study, we identified the exogenous miRNAs from rapeseed bee pollen in mice blood using RNA-seq technology. We found that miR-166a was the most highly enriched exogenous plant miRNAs in the blood of mice fed with rapeseed bee pollen, followed by miR-159. Subsequently, RT-qPCR results confirmed that these two miRNAs also can be detected in rapeseed bee pollen. Our results suggested that food-derived exogenous miRNAs from rapeseed bee pollen could be absorbed in mice and the abundance of exogenous miRNAs in mouse blood is dependent on their original levels in the rapeseed bee pollen.